3D printing interface-modified PDMS/MXene nanocomposites for stretchable conductors. (1st August 2022) - Aakyiir, Mathias; Tanner, Brayden; Yap, Pei Lay; Rastin, Hadi; Tung, Tran Thanh; Losic, Dusan; Meng, Qingshi; Ma, Jun
Highlights: Surface modification of Ti3 C2 Tx MXene ink for 3D printing. Improved interface interaction for PDMS/MXene stretchable conductors. 3D printing of stretchable conductors with high self-supporting behaviour. PDMS/MXene construct with appropriate stress-strain relations and electrical conductivity. Abstract: Additive manufacturing has rapidly evolved over recent years with the advent of polymer inks and those inks containing novel nanomaterials. The compatibility of polymer inks with nanomaterial inks remains a great challenge. Simple yet effective methods for interface improvement are highly sought-after to significantly enhance the functional and mechanical properties of printed polymer nanocomposites. In this study, we developed and modified a Ti3 C2 MXene ink with a siloxane surfactant to provide compatibility with a polydimethylsiloxane (PDMS) matrix. The rheology of all the inks was investigated with parameters such as complex modulus and viscosity, confirming a self-supporting ink behaviour, whilst Fourier-transform infrared spectroscopy exposed the inks' reaction mechanisms. The modified MXene nanosheets have displayed strong interactions with PDMS over a wide strain amplitude. An electrical conductivity of 6.14 × 10 −2 S cm −1 was recorded for a stretchable nanocomposite conductor containing the modified MXene ink. The nanocomposite revealed a nearly linear stress-strain relationship and a maximum stress of 0.25 MPa. Within 5% strain, the relative resistance change remained below 35% for up to 100 cycles, suggesting high flexibility, conductivity and mechanical resilience. This study creates a pathway for 3D printing conductive polymer/nanomaterial inks for multifunctional applications such as stretchable electronics and sensors.